I6dians of the Northwest - Press, Petra 1832-1898.; Sir, 1820-1914 (Milwaukee, WI Gareth Stevens Publishing, 2000)
Describes the group rituals, social customs, and governing systems of the Kwakiutl, Spokane, Yakima, Tlingit, and other tribes.
Issued also with marginal illustrations.
Keywords: Indians -- Northwest U.S.; Series: The Native Americans